À moda da casa : a cozinha como espaço físico e simbólico em O arroz de Palma, Por que sou gorda, mamãe? e Quarenta dias - Cardoso, Betina Mariante (2016)
This dissertation aims to analyze the kitchen as a physical and symbolic space within the context of three works of contemporary Brazilian literature: Francisco Azevedo’s O arroz de Palma (2008), Cintia Moscovich’s Por que sou gorda, mamãe? (2006) and Maria Valeria Rezende’s Quarenta dias (2014). In each work, kitchen is related to one of the following three paradigms, respectively: memory, pleasure and autonomy. Thus, this study consists of three chapters entitled "Kitchen and Memory", "Kitchen and Pleasure", and " Kitchen and Autonomy". Our goal is to understand how the kitchen is described in the narratives of the corpus, in the context of the selected topics. Elements of psychiatric phenomenology, sociology and food history are presented in connection with contemporary Brazilian literature.